HTML, CSS, & JavaScript mobile development for dummies - Harrel, William (Wiley, 2011)
Master the art of designing web pages for mobile devices--a site for small screens! When designing a web page for mobile devices, the big thing is--think small! Your objective is to provide what the mobile user wants without losing the "wow" in your website. This book shows you how to do it using three key technologies. Soon you'll be building mobile pages with forms, quizzes, appropriate graphics, shopping carts, and more! Think mobile--consider screen size, lack of a mouse, duel orientation screens, and mobile browsers. Know your audience--understand how people use the mobile web and how their habits differ from those of desktop users Get interactive--optimize multimedia files and develop contact forms that encourage visitors to interact with your site. Latest and greatest--maximize the new features of HTML5 and CSS3, automate your site with JavaScript, and use WebKit Extensions. Be sure they find you--make your mobile site both easily searchable and search engine-friendly. Open the book and find: Why you should know WURFL ; A system for keeping your site up to date ; All about bitmap and vector images ; Easy ways to adjust your site for different devices ; Powerful SEO ideas to get your site noticed ; Tips for creating a mobile shopping cart ; How to take your blog theme mobile ; Ten mobile CSS-friendly apps and widgets Learn to: Use standard web tools to build sites for iPhone, iPad, BlackBerry, and Android platforms ; Optimize sites for all mobile devices ; Accommodate different mobile browsers and security features ; Take advantage of HTML5